Issue Mapping for an Ageing Europe - Rogers, Richard, 1965- (Book collections on Project MUSE., 2015)
In Europe, the old will soon outnumber the young-an event that will threaten the stability of both pension and healthcare systems while also changing the migration patterns of those who need and provide care. This volume uses new media technologies to map this urgent issue. The latest theoretical approaches to issue mapping are put into practice via online mapping techniques, demonstrations of ways to explore the complex issue of demographics, and discussion of the debates surrounding available online data. By employing websites of non-governmental organizations, search engine queries identifying cultural philosophies about ageing, and more, the contributors to this volume have defined the agenda for ageing issues throughout Europe.